Development of Teleological Explanations in Peruvian Quechua‐Speaking and U.S. English‐Speaking Preschoolers and Adults. Issue 3 (May 2016) - Sánchez Tapia, Ingrid; Gelman, Susan A.; Hollander, Michelle A.; Manczak, Erika M.; Mannheim, Bruce; Escalante, Carmen
Abstract : Teleological reasoning involves the assumption that entities exist for a purpose (giraffes have long necks for reaching leaves). This study examines how teleological reasoning relates to cultural context, by studying teleological reasoning in 61 Quechua‐speaking Peruvian preschoolers ( M age  = 5.3 years) and adults in an indigenous community, compared to 72 English‐speaking U.S. preschoolers ( M age  = 4.9 years) and university students. Data were responses to open‐ended "why" questions ("Why is that mountain tall?"). Teleological explanations about nonliving natural kinds were more frequent for children than adults, and for Quechua than U.S. participants. However, changes with age were importantly distinct from differences corresponding to cultural variation. Developmental and cultural differences in teleological explanations may reflect causal analysis of the features under consideration.